Needs analysis in an EAP course: A case study - Mohd Basari, Shahrul Nizam (Academia Industry Networks, 2019)
This case study was done to investigate academic writing at a public university, in relation to student writing needs and the context of academic writing in a writing course at a public university in Malaysia. The study employed the complementarity mixed-method design, where questionnaires and interviews were used to collect the data. The total number of respondents for the questionnaire was 157 (26 EAP lecturers, 22 engineering lecturers, 17 human sciences lecturers and 92 EAP students from the engineering and human sciences faculties). Interviews were done with 15 EAP lecturers, three engineering lecturers, four human sciences lecturers, four EAP/engineering students and four EAP/human sciences students. The objectives of the study were to investigate the EAP lecturers’, the faculty lecturers’, and students’ perceptions of student academic writing needs and the EAP course. The results of the case study revealed that the EAP, engineering and human sciences lecturers as well as the EAP/engineering and EAP/human sciences students had similar and different perceptions with regard to student academic writing needs. Secondly, the majority of the EAP lecturers and students have a positive view towards the EAP course. The present needs (PSA) and the target needs (TSA) that have been identified from the findings can be used as a source of information for other language centres for their academic writing courses. As a start, since the findings also relate the identified needs with specific faculties (engineering and human sciences), this information can be used as a guide to determine the syllabus of a writing course for the related faculties.